Macronutrients in Marandu Palisade Grass as Influenced by Lime, Slag, and Nitrogen Fertilization - Fonseca, I. M. [UNESP]; Prado, R. M.; Nogueira, T. A. R.; Barbosa, J. C. [UNESP] (Taylor & Francis Inc, 2011)
Soil acidity is one of the main limiting factors for the growth of pasture grasses in Brazilian soils. In addition to lime, slag can be used to correct soil acidity and help plants to absorb nutrients in adequate amounts. The objective of this experiment was to evaluate, under greenhouse conditions, the effects of slag and lime plus nitrogen (N) on marandu palisade grass plants' nutritional status as well as the absorption of macronutrients submitted to two cuts. The treatments consisted of two corrective materials (slag and lime), three corrective material rates (0.81, 1.61, and 3.22 g dm-3 of ECaCO3), three N rates (75, 150, and 300 mg dm-3) plus a control treatment, with four replications. Macronutrient contents in the forage plants were found to be present in adequate levels. The mean value of N accumulated in the shoot was 40.1 mg per plant, phosphorus (P) was 4.6 mg per plant, potassium (K) was 38.6 mg per plant, calcium (Ca) was 7.3 mg per plant, magnesium (Mg) was 6.7 mg per plant, and sulfur (S) was 3.5 mg per plant at the first cut. At the second cut, the nutrient accumulations values were N 50.8 mg per plant, P 6.3 mg per plant, K 20.7 mg per plant, Ca 21.6 mg per plant, Mg 24.0 mg per plant, and S 4.7 mg per plant. Macronutrients accumulation in the shoot of grass increased with the addition of both the correctives as well as the N rates.
Keywords: Brachiaria brizantha; calcium silicate; liming; metallurgical residue; nitrogen fertilization